(untitled) (Revista de História Regional, 2007)
This article suggests a discussion about catholic action in the city of Taubaté, State of São Paulo, in the middle of the 20th. century through the Press, particularly O Lábaro, journal with great regional circulation since it was created in January, 1910. In the decade of 1950, in the past century, this cited journal sponsored a progression toward modernization of its technical equipment and incursion on the advertising market. At the same time, it was qualitative in defending its dogmatic and ideologic centenary centre. In the middle of the tension between tradition that preserves and modernity, that in some cases, moves forward the local church incursioned on urban arena and was present through an articulated and systematic action. The result was the strengthening of a cultured and militant élite intervening in the heart of the city.